PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN MELALUI TURNOVER INTENTION - Galih Ray Cakrawinata; Hermina, Nurul (LPPM Universitas Sangga Buana, 2024)
This research aims to determine the influence of leadership style and job satisfaction on employee performance through turnover intention directly and indirectly. The population and sample in this research were all PT Toyobo Manufacturing Indonesia employees, totaling 171 employees. The data collection method uses a questionnaire which is measured using a Likert scale. Data processing was carried out with the help of the Statistical Program for Social Science (SPSS) version 25. Descriptive analysis and verification analysis were the methods used in this research. The results of the descriptive analysis explain that leadership style, job satisfaction, and employee performance can be categorized as good, and turnover intention is categorized as very bad. The results of hypothesis testing state that leadership style has a positive and significant effect on employee performance both partially and simultaneously. It can be said that job satisfaction has no direct influence on employee performance, but the turnover intention variable has succeeded in mediating the job satisfaction variable so that it can influence employee performance at PT Toyobo Manufacturing Indonesia. The regression equation obtained in this research is Z = 15.170 + 0.116 X1 + 0.089 X2 +(- 0.385) Y.